Participación del Estado Peruano en la restauración de la dignidad e integridad psíquica y física de las víctimas de violación sexual - Ayapi Bazan, Margarita (2019)
ABSTRACT This present thesis entitled: "PARTICIPATION OF THE PERUVIAN STATE IN RESTORING THE DIGNITY AND INTEGRITY OF VICTIMS OF SEXUAL VIOLATION"; Addresses the issue of how the Peruvian state has participated in the restoration of the dignity and physical and mental integrity of victims of rape in the Trujillo District during the years 2016-2017; With the general objective of determining how the Peruvian state has participated in the restoration of the dignity and physical and mental integrity of victims of rape in the Trujillo District during the years 2016-2017. In order to formulate and contrast our hypothesis, in the sense that "the Peruvian state in the Trujillo district during the years 2016 - 2017 has participated in the restoration of the dignity and physical and mental integrity of victims of rape In a deficient way, since it does not have mechanisms properly organized and developed for that purpose "; Has been worked on in the Theoretical Framework, chapters referred to the Fundamental Rights in the crimes of Sexual Violence, Rape and Sexual Abuse, Victimology: The victim of sexual abuse and the Treatment Policies of the Victim of Sexual Abuse (Peru and in Exterior). The universal method was also used, the general method covering the deductive and inductive methods, and the specific method containing the synthetic, hermeneutical and analytical methods, where one can study decomposing each of the elements that make up the Problematic about the participation of the Peruvian state in the restoration of the dignity and physical and mental integrity of victims of rape in the Trujillo district during the years 2016 – 2017. The present investigation concludes by indicating that the Peruvian State in the Trujillo District during the period 2016 - 2017 has participated with the creation of Area of Defense to the Victim, Unit of Victims and Witnesses, and Units of psychological, social and legal support ( CEM); However, these mechanisms have proved to be insufficient to provide reparation to the victim of rape in a comprehensive manner, since the State is required to provide a budget and resource for these entities to improve restorative work.